Analyze the relationship between budget revernue and economic growth of Luang Prabang province from 2006 - 2020 - AHDHARN, Amphone; CHANTHAVONE, Thongphanh; XIONGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Through a study on the topic, analysis of relationship between budget revenue (R) and economic development (GDP) of Luang Prabang from 2006 to 2020. The purpose of study: the state of fiscal revenue collection and economic growth of Luang Prabang province and analyze the short-term and long-term relationship between the causes and results between fiscal revenue and economic growth of Luang Prabang province, the results of the study found that: The state revenue of Luang Prabang were growing from 2006 - 2020, with an average growth rate of 15.98% per year, the year when the state revenue grew higher than its peers was 2007 with a growth rate of 33.07%, down to 2008 and 2012, with growth rates equal to 30.64% and 28.78% respectively, For the total gross domestic product (GDP) of Luang Prabang from 2006 - 2020, The total value is 70,952,231.03 million kip, an average of 4,730,148.74 million LAK with an average growth rate of 10.33% per year. The results of the co-integration test for long-run correlation, the coefficient value is a positive and rejected null hypothesis with statistical significance level of 0.05, which means, when the state revenue of Luang Prabang is increasing, it will effect on economic growth of Luang Prabang increases in the long-run. The results of the short-run relationship test are only the case of GDP as a dependent variable, the test results show that the coefficient valve has a negative and rejected the null hypothesis with a statistical significance level of 0.05. It shows that the state revenue and the gross domestic product (GDP) of Luang Prabang have a negative short-run relationship. But the results of the adjustment test show that there is an adjustment from the short-run equilibrium relationship to the long-term equilibrium relationship with an adjustment speed of -0.5755. For the granger causality test, it is seen that the Gross Domestic Product (GDP) of Luang Prabang is the causes for state revenue (R) in Luang Prabang Province to change.